Jane Tolmach for Assembly 36th District (1976)
This March 19, 1976 press release announces that Assembly Majority Whip Joseph Montoya will be the special guest at a Jane Tolmach campaign fundraising barbecue on April 25 at Steckel Park. Tolmach highlights Montoya's leadership roles in the Assembly, including his work on education, agriculture, and as Chair of the Chicano Caucus, noting his potential influence on establishing a four-year college in Ventura County. She emphasizes their shared background in social services and expresses hope for a productive working relationship in Sacramento. The release provides event details and encourages advance reservations to support the campaign.